Interventions to improve pharmacists’ competency in chronic disease management: a systematic review of randomized controlled trials - Farida Rendrayani; Auliasari M. Utami; Widya N. Insani; Falerina Puspita; Sofa D. Alfian; Thang Nguyen; Irma M. Puspitasari (BMC Medical Education)
Abstract Introduction Effective chronic disease management (CDM) is vital for addressing chronic disease challenges. Given the importance of ensuring pharmacists’ competence in CDM, interventions targeting knowledge, skills, and attitudes are essential. Therefore, a comprehensive and up-to-date study is needed to analyze these interventions’ effect and potential development. Categorizing the interventions based on the Effective Practice and Organization of Care (EPOC) taxonomy is essential for better informing policymakers. The objectives of this systematic review were to identify interventions to improve pharmacists’ competency in chronic disease management based on the EPOC taxonomy and summarize their effectiveness. Methods Following methods in the Cochrane Handbook, a systematic search was conducted up to April 2024 on MEDLINE and Scopus. The inclusion criteria were an intervention study with a randomized controlled trial (RCT) design published in English, targeting pharmacists, and measuring knowledge, skills, and attitudes in aspects of CDM. The risk of bias was assessed using Cochrane’s RoB 2 tool for either randomized or cluster-randomized trials. Findings are reported narratively and align with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Results We included 11 RCT studies that focused on various aspects of CDM among community and hospital pharmacists. Implementation strategies and combined implementation strategies–delivery arrangements interventions were identified. Six implementation strategies interventions consistently yielded effective results, with scores ranging from 0.99 to 9.17 (p < 0.05). However, the other two implementation strategies interventions reported mixed results, with no significant improvements in knowledge or skills. Two implementation strategies-delivery arrangements interventions showed improvements, with score differences ranging from 4.5% (95% CI: 1.6%-7.4%) to 30% (95% CI: 29%-40%). Conversely, one implementation strategies-delivery arrangements intervention showed no significant improvement. The risk of bias assessment revealed varying levels of bias across the studies. Conclusions Implementation strategies and combined implementation strategies–delivery arrangements interventions improved pharmacists' competency in CDM. Most interventions consistently resulted in significant improvements in pharmacists' knowledge, skills, and attitudes. These findings underscore the potential of tailored, competency-based interventions to improve pharmacist competencies in CDM. Policymakers can use these insights to create guidelines and policies that promote ongoing professional development for pharmacists.